2018
DOI: 10.3892/br.2018.1111
|View full text |Cite
|
Sign up to set email alerts
|

Second‑line triple therapy in failures with vonoprazan‑based triple therapy for eradication of Helicobacter pylori

Abstract: Abstract. Gastric acid inhibition during treatment is important for the eradication of Helicobacter pylori (H. pylori) infection. A novel potassium-competitive acid blocker, vonoprazan (VPZ), has been demonstrated to achieve high eradication rates; however, the efficacy of second-line treatment in failures of VPZ-based triple therapy has not been well studied.The aim of the current study was to determine the efficacy of VPZ in a first-line regimen for H. pylori eradication, and the efficacy of a second-line re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…We searched for comparative studies that examined the rate of H. pylori eradication with vonoprazan-based triple therapies and PPI-based triple therapies using the key words "vonoprazan" and "pylori" in PubMed on November 1, 2018. Excluding the studies that did not show detailed data, 6 prospective studies (21-26) and 12 retrospective studies (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) were assessed. The results of the studies are presented in Table 1.…”
Section: H Pylori Eradication Rate With Vonoprazanmentioning
confidence: 99%
See 1 more Smart Citation
“…We searched for comparative studies that examined the rate of H. pylori eradication with vonoprazan-based triple therapies and PPI-based triple therapies using the key words "vonoprazan" and "pylori" in PubMed on November 1, 2018. Excluding the studies that did not show detailed data, 6 prospective studies (21-26) and 12 retrospective studies (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) were assessed. The results of the studies are presented in Table 1.…”
Section: H Pylori Eradication Rate With Vonoprazanmentioning
confidence: 99%
“…Second, we must consider the various patterns of antibiotic resistance of H. pylori among regions. The Japanese studies described above investigated roughly the same eradication regimens: vonoprazan 20 mg + amoxicillin 750 mg + clarithromycin 200/400 mg or metronidazole 250 mg, twice (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). In Japan, the rate of clarithromycin resistance of H. pylori is more than 30%, whereas that of metronidazole resistance is less than 5% (55).…”
Section: Can Vonoprazan-based Triple Therapy Be Applied To Other Popumentioning
confidence: 99%
“…In recent years, several studies have compared eradication rates between VPZ-containing and PPI-containing triple therapies across centers in Japan. As shown in Table 2, up until September 2018, 23 reports had investigated the efficacy of first-line VPZ-containing therapy (21 reports for VPZ/AMX/CLR and 2 reports for VPZ/MNZ/CLR) (Matsumoto et al, 2016; Murakami et al, 2016; Noda et al, 2016; Shichijo et al, 2016; Shinozaki et al, 2016, 2018; Suzuki et al, 2016; Tsujimae et al, 2016; Yamada et al, 2016; Kajihara et al, 2017; Katayama et al, 2017; Maruyama et al, 2017; Nishizawa et al, 2017; Ono et al, 2017; Sakurai et al, 2017; Sue et al, 2017a,b, 2018a; Sugimoto et al, 2017; Tanabe et al, 2017, 2018; Mori et al, 2018; Ozaki et al, 2018), and 19 reports had compared the efficacy between VPZ-containing therapy and PPI-containing therapy, including 3 randomized control trials (Murakami et al, 2016; Maruyama et al, 2017; Sue et al, 2018a) and 16 non-randomized retrospective cohort trials (Matsumoto et al, 2016; Noda et al, 2016; Shichijo et al, 2016; Shinozaki et al, 2016; Suzuki et al, 2016; Tsujimae et al, 2016; Yamada et al, 2016; Kajihara et al, 2017; Nishizawa et al, 2017; Ono et al, 2017; Sakurai et al, 2017; Sue et al, 2017a,b; Mori et al, 2018; Ozaki et al, 2018; Tanabe et al, 2018).…”
Section: First-line Vonoprazan-containing Eradication Therapymentioning
confidence: 99%
“…As shown in Table 2, first-line triple VPZ-containing therapies (VPZ/AMX/CLR) therefore show superior efficacy in Japanese individuals in terms of H. pylori eradication compared to PPI-containing therapies (Matsumoto et al, 2016; Murakami et al, 2016; Noda et al, 2016; Shichijo et al, 2016; Shinozaki et al, 2016, 2018; Suzuki et al, 2016; Tsujimae et al, 2016; Yamada et al, 2016; Kajihara et al, 2017; Katayama et al, 2017; Maruyama et al, 2017; Nishizawa et al, 2017; Ono et al, 2017; Sakurai et al, 2017; Sue et al, 2017a,b, 2018a; Sugimoto et al, 2017; Tanabe et al, 2017, 2018; Mori et al, 2018; Ozaki et al, 2018). According to a grading system established by Graham et al (2007) the 69.1–75.0% eradication rate of PPI-containing therapies constitutes an unacceptable grade (grade F).…”
Section: First-line Vonoprazan-containing Eradication Therapymentioning
confidence: 99%
“…67 Elsewhere in Japan, another study found vonoprazan triple therapy to be significantly more effective than standard therapy as first line (91% vs 85%) but not second line (87% vs 88%). 68 Two trials looked at the introduction of vonoprazan-based therapy as third line for patients who had failed two courses of PPI-based therapies. The first, a randomized controlled trial showed 76.8% eradication for vonoprazan, amoxicillin, and sitafloxacin, compared to 53% when PPI was used with those antibiotics.…”
Section: Vonopr a Z Anmentioning
confidence: 99%